Mining Employees Safety and the Application of Information Technology in Coal Mining: Review - Yang, Li; Birhane, Getnet Engeda; Zhu, Junqi; Geng, Jichao (Frontiers in Public Health, 2021)
Background: Though safer modern underground mining methods and automation have been introduced, mine accidents still cause loss of lives, time, and money. This paper aims to analyze in detail the causes of safety and environmental issues in the coal mining industry, as well as the impact of IoT on coal mining. Method: A systematic review was conducted. A comprehensive search involving Web of Science, Google Scholar, Scopus, and Science direct databases was conducted using a combination of the following keywords: mining accidents, coal mining injuries, human error in mining, intelligent mining, etc. The inclusion criteria: (1) the study was published between January 2000 and June 2020; (2) the participants were coal mining employees/ coal mining accidents and accidents were work-related; (3) the study focused on identifying causes of coal mining safety issues or accidents, factors that influence unsafe behaviors and accidents in coal mining, coal mining rescue management, coal mining rescue plan, coal mining environmental impact, mining information technology, intelligent mining; (4) the study was published in a refereed journal; (5) the study was written in English. In this paper, articles were retained if they were original studies. Results: A total of 51 papers were reviewed in detail. Safety issues in coal mining and the impact of IoT were identified and categorized into three main factors: general safety issues, environmental factors, and mining information technology. Recently, the coal mines had become mechanized and automated leading to improved safety, productivity, and cost. However, Human factors such as lack of appropriate skill, lack of experience, perceptual error, and unsafe behaviors, as well as lack of detailed emergency rescue plan were the leading causes of coal mining injuries. Furthermore, abandoned mining sites' carbon emission is greater than active sites. Conclusion: The study recommends further research to be conducted using different psychological models to understand human factors and design effective safety management systems. And the environmental impact of abandoned mining sites should be given due attention.